An analysis of students voices towards a regional LMS for ELT in Indonesian Islamic schools - Amalia, Syahara Dina; Fata, Ika Apriani; Marhaban, Saiful; Huda, Ismul; Saidu, Abdulhakim (Studies in English Language and Education, 2025)
The current study examined students perspectives on the use of one of the regional learning management systems (LMS), E-Belajar (hereafter EB), at two Islamic boarding schools in Aceh, Indonesia. Fifty EFL Islamic boarding school students agreed to participate in this study. This study used a mixed method design, combining surveys and interviews. The data from the questionnaire was analysed quantitatively. Meanwhile, thematic analysis was performed on the interview data. The results revealed both good and negative attitudes of EB in ELT. Positive replies indicate that EB improved English comprehension and promoted autonomous learning, assisted students in completing English tasks on time by using the alert feature as a reminder, developed enjoyable and engaging learning activities using videos and online games, and encouraged students confidence in expressing ideas. However, negative voices highlighted the teachers failure to advise students on how to use EB properly, resulting in incorrect task submission. Students also preferred in person learning, and students had trouble communicating effectively. Students further pointed out that EB did not enhance listening skill, reading skill, speaking skill, writing skill, or grammar understanding significantly; only few students believed that EB helped promote English language skills, indicating that further efforts through EB was required. Students were also unable to access certain EB services, such as e-counselling and e-monitoring. Furthermore, dormitories have limited access to the internet. These circumstances became another drawback for students.